Exploring The Potential of Solid Lipid Nanoparticles to Improve the Oral Bioavailability of Niclosamide: A Pharmaceutical and Stability Evaluation - Rehman, Maqsood ur; Aziz Ur Rahman; Hussain, Ubaida; Saeed, Akif; Ali, Rashid (Indus Journal of Bioscience Research, 2025)
Background: Niclosamide, a BCS Class II drug with poor water solubility, suffers from limited oral bioavailability, necessitating innovative delivery strategies to enhance its therapeutic efficacy. Objective: This study aimed to develop and optimize solid lipid nanoparticles (SLNs) of Niclosamide to improve its solubility, stability, and bioavailability. Methods: Niclosamide-loaded SLNs were prepared using the solvent emulsification-diffusion method. Optimization was performed by varying lipid-to-drug ratios, surfactant concentrations, and stirring times. The SLNs were characterized for particle size, polydispersity index (PDI), zeta potential, entrapment efficiency (EE), drug loading capacity (DLC), and morphology. Stability studies were conducted at refrigerated and room temperatures for three months. In vitro drug release was assessed using the dialysis bag method, and in vivo pharmacokinetics were evaluated in rabbits using high-performance liquid chromatography (HPLC). Results: Optimized SLNs (NSED-2) showed a particle size of 208.6±2.2 nm, PDI of 0.376±0.04, and zeta potential of -34.11±1.2 mV. EE and DLC were 85.4±0.04% and 3.18±0.04%, respectively. In vivo, NSED-2 demonstrated a 2.04-fold increase in peak plasma concentration (Cmax: 4.07±0.124 µg/mL) and a 10.59-fold increase in area under the curve (AUC0→24: 21.19 µg·h/mL) compared to the marketed product. Conclusion: Niclosamide-loaded SLNs significantly enhanced drug solubility, stability, and oral bioavailability, offering a promising platform for improving the delivery of poorly water-soluble drugs.